Parametric numerical study of Savonius wind turbine interaction in a linear array. (December 2017) - Mereu, R.; Federici, D.; Ferrari, G.; Schito, P.; Inzoli, F.
Abstract: This work focuses on Savonius turbine numerical modeling and mutual turbine interaction in a linear array farm. Two-dimensional Computational Fluid Dynamics modeling was carried out using the open source solver OpenFOAM. Results are compared with available experimental data and three-dimensional CFD modeling. The influence of main parameters, such as the distance between adjacent turbines, the wind incidence angle and the number of turbines is investigated and the linear array efficiency is defined. The obtained results show a performance increase as the distance between the turbines reduces, higher efficiency for small wind incidence angles, and a larger number of turbines. Highlights: CFD study to characterise the interaction effect between multiple Savonius turbines. URANS modeling approach with k-omega SST turbulence model in OpenFOAM code. Analysis at different distance between rotors and the number of turbines. Increase in performance with the reduction of the distance between rotors. Influence of wind incident direction and number of turbines on the array performance.